Imperatives Translationa Technique in Subtitle: A case Study of Frozen II - Rachel Beny Andani; Salsabila Cintia Setiadery; Fitry Alfarisy (Universitas Sebelas Maret, 2023)
Translation is the process of delivering messages from the source language into the target language so that it can be reached by the reader. Translator activities also occur in films. Film is an audiovisual media that is very popular with the public. In this study, the author focuses more on the translation of the subtitles in the Frozen II film. This study aims to describe the technique of translating imperative sentences with subtitles in the Frozen II film and to describe the most dominant translation techniques in the subtitles of the Frozen II film. This study uses qualitative methods and data collection. This study uses 18 translation techniques belonging to Molina Dan Albir (2002). The results showed the dominance of the use of literal techniques in imperative sentence subtitles as much as 39 data or 63.93%. In future research, it is hoped that there will be further research with a wider scope.